CAUSA EFFECTIVENESS IN ESTABLISHING SHARIA AGREEMENTS - Mhd Nasir Sitompul (Proceeding International Seminar of Islamic Studies, 2021)
According to experts of premodern Islamic law, the pillars of the contract consist of only 3 elements, namely the parties, the declaration of will, the object of the contract. Then in modern times, Islamic law experts develop a new view by adding a new pillar that is the purpose of the agreement to the existing pillars of the contract. Unfulfilled agreement may result in the cancellation of the agreement. The law of the contract referred to in the Islamic treaty law is the result of the law arising from the distinguishable contract, namely the basic law of the contract and the additional law of the contract that is the rights and obligations arising from the contract. The consequences of the law were formulated using the theory of causation in the islamic covenant law based on the concept of legal causation. The research method used in this research is empirical juridical which is descriptive. Empirical juridical research is conducted by internalizing the problem by combining legal materials that are secondary legal materials with primary data. Descriptive research is research that only describes the state of the object or its events without an intention to draw generally valid conclusions. Islamic law states the nullity of the alliance in accordance with its rules, namely if it cancels something, cancels what is contained therein. If one of the conditions is void, the contract is canceled and if the contract is void, all legal and alliance consequences arising there from it will be void. According to the view of latin law whose attention is not to the source that gave birth to the alliance, latin law is forced to create the doctrine of the kausa in alliances born of agreements that are connected to each other in order to be declared annulment. in Islamic law the annulment is sufficient to state that the object of the contract without seeing from any party in the form of an act of evil can not accept the contract.Keywords: Akad, causa, agreement.